Derivative four-fermion model, effective action and bumblebee generation - R. Araújo; T. Mariz; J. R. Nascimento; A. Yu. Petrov (European Physical Journal C: Particles and Fields)
Abstract In this paper, we study the one-loop effective potential of a derivative four-fermion model. As a result, an exact bumblebee-like potential is radiatively generated. Afterwards, we generalize our study for a finite temperature case and explicitly demonstrate the possibility of phase transitions allowing for the restoration of the Lorentz symmetry. We also investigate the low-energy effective action, from which we obtain the usual kinetic term and the corresponding bumblebee potential.